Effect of planting date and density on calendula and peppermint herbs - Mohammadian, Rahim; Tahmasebpour, Behnam; Samimifar, Peyvand (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
A factorial experiment was conducted with a completely randomized design to evaluate the effects of planting date and density on calendula herbs and peppermint. It had 3 replicates and was done in Khosroshahr research farm, Tabriz in 2006. Under studied factors were: 3 planting dates (10 May, 25 May and 10 June) in 4 densities (25, 35, 45, 55) of the plant in square meters. The results of variance a nalysis showed that there was 1% probability significant difference between the effects of planting date and bush density on the leave number, bush height and the bush dry weight. But the mutual effect of the plant date in mentioned traits density was insignificant. Regarding the traits mean comparison, the total maximum dry weight was about the 55 bush density in mm. Also, the bush high density in mm causes the bush growth and its mass reduction. When there is the density grain, the flower number will increase due to bush grain in surface unit. Overall, we can conclude that 10 June planting and 45 bush density in mm is the most suitable items and results in favored production with high essence for these crops.